2004
DOI: 10.1128/aem.70.4.1990-1998.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk between 2,4-Diacetylphloroglucinol-Producing Biocontrol Pseudomonads on Wheat Roots

Abstract: The performance of Pseudomonas biocontrol agents may be improved by applying mixtures of strains which are complementary in their capacity to suppress plant diseases. Here, we have chosen the combination of Pseudomonas fluorescens CHA0 with another well-characterized biocontrol agent, P. fluorescens Q2-87, as a model to study how these strains affect each other's expression of a biocontrol trait. In both strains, production of the antimicrobial compound 2,4-diacetylphloroglucinol (DAPG) is a crucial factor con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 40 publications
3
56
0
Order By: Relevance
“…Moreover, a steady decrease of DAPG levels at later growth stages that is indicative of DAPG degradation occurs in cultures of strains CHA0 (Fig. 3) (3, 31, 39), Pf-5, Q2-87, and F113 (8,10,27). Together, these observations suggest that an active mechanism of DAPG degradation is a conserved feature among DAPG-producing pseudomonads.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, a steady decrease of DAPG levels at later growth stages that is indicative of DAPG degradation occurs in cultures of strains CHA0 (Fig. 3) (3, 31, 39), Pf-5, Q2-87, and F113 (8,10,27). Together, these observations suggest that an active mechanism of DAPG degradation is a conserved feature among DAPG-producing pseudomonads.…”
Section: Discussionmentioning
confidence: 69%
“…They include the housekeeping factor RpoD, the stationary-phase and stress response factor RpoS, and the alternative factor RpoN (31,36,38). In addition, many abiotic and biotic environmental factors may modulate levels of DAPG production, including different carbon and nitrogen sources, transition metal ions and other minerals, and metabolites released by bacteria, fungi, and plants (12,27,28). For instance, DAPG biosynthesis in P. fluorescens strains CHA0 and Pf-5 is negatively affected by pyoluteorin, another antifungal compound synthesized by these bacteria (3,8,39).…”
mentioning
confidence: 99%
“…seudomonads are well-studied plant-growth-promoting rhizobacteria (PGPR) that have long been recognized for their role in biological control of different plant pathogens (1)(2)(3)(4)(5). The adaptability of certain strains to inhabit the rhizosphere, the root surface, and sometimes the roots themselves is indispensable to their disease suppression capacities (6,7).…”
mentioning
confidence: 99%
“…For example, the expression of important biocontrol genes such as DAPG or HCN biosynthetic genes in the rhizosphere is modulated by biotic factors such as fungi and other bacteria present in the rhizosphere and the secondary metabolites they release (7,19,27,29,32). Moreover, it has been observed that the plant species and cultivar as well as the physiological stage of the plant can influence the expression of biocontrol genes and the production of antimicrobial metabolites (4,7,19,32,35).…”
mentioning
confidence: 99%